PERANCANGAN BRAND AKTIVASI DAN MEDIA PROMOSI UNTUK APLIKASI UNDANGAN PERNIKAHAN “OURSTORIES” - Evelyn Aloysia; Ferryanto Chia (Universitas Ciputra Surabaya, 2016)
This design is made in order to make a brand activation and promotional media for Ourstories wedding invitation apps. Ourstories is a business that works in the field of wedding invitation based on digital apps, so it requires the brand activation and promotion of the right media so it can be recognized by the target market of Ourstories. Brand activation strategies undertaken by Ourstories is following a wedding exhibition and event promotion through social media.